Effect of Induced Charge on the Passivity and Passivity Breakdown of 304LN Stainless Steels - Gargi Roy Chowdhury; P. K. Mitra (Advances in Materials Science and Engineering)
Passivity breakdown of stainless steel by pitting in chloride environment is believed to occur at point at zero charge (pzc). So, the nature and quantity of charge on the surface plays a very important role on the breakdown of passivity, as chloride ion adsorption depends on that. In this work a DC potential was maintained between aluminium and graphite electrodes, and the aluminium electrode, in turn, was kept in the vicinity of the working electrode in the potentiostatic circuit. Both positive and negative polarity was applied on aluminium to attract or repel chloride ions in the vicinity of the working electrode. Chloride adsorption pattern on the stainless steel electrode got drastically altered due to application of DC potential on the aluminium-graphite circuit.